MAKNA MITOLOGIS LEGENDA JAKA POLENG - DEVI, WIKA SOVIANA (Fakultas Ilmu Budaya Universitas Diponegoro, 2008)
Jaka Poleng legend is a folklore with several versions developed in the northern coastal area of Brebes. Comparing the oral and written versions of Jaka Poleng story resulted in some differences in the transformation of Jaka Poleng into a snake. The public response of the mythological meaning of the Jaka Poleng story is the reaction toward the existence of Jaka Poleng figure. This figure is believed to remain exist in one room in the Pendopo Kabupaten of Brebes. Some believe that Jaka Poleng is the guardian of Brebes people.